Ravnanja davčnih zavezancev v razponu od dovoljenega davčnega načrtovanja do kazensko pregonljive davčne utaje - Ravljen, Marko (Podjetje in delo, 2018)
Conduct of Taxable Persons, Ranging from Allowed Tax Planning to Criminal Prosecuted Tax Evasion Abstract: The purpose of the presented paper is to highlight the particular situation of the tax law in the legal system. Tax law is a separate legal matter and not a branch of either civil or criminal law; tax law is based (also) on its own concepts (such as income, assets, turnover), makes its own conclusions and develops its own doctrines. Civil and tax law are two related areas of the law that take under consideration (fully or partially) the same concrete factual situation from a different perspective and under different values. Tax law is not a result of civil law. The author also notes that Slovenian authors give inconsistent explanations of the analysed legal area of "dodging of tax-payment" (Germ. Steuerausweichung), which, as a broad term, covers the entire field of the individual's conduct from legal to criminal. Therefore, due to the need to set up a consistent terminology, the author puts forward (in particular, on the basis of German law) new foundations, and uses the term "tax planning" to define legal conduct, the term "tax avoidance" to define the disputed behaviour, which however does not constitute a criminal offense, and the term "tax evasion" ("tax fraud") to define a purely criminal offense. The author analyses this theoretical view in more detail by presenting the theoretical example of "taxation on windows" and its practical solutions.
Keywords: civilno pravo; davčna izognitev; davčne utaje; davčno pravo; davčno zaobidenje; pravičnost